The effect of cognitive load, ego depletion, induction and time restriction on moral judgments about sacrificial dilemmas: a meta-analysis - Rehren, Paul (Frontiers in Psychology, 2024)
Greene's influential dual-process model of moral cognition (mDPM) proposes that when people engage in Type 2 processing, they tend to make consequentialist moral judgments. One important source of empirical support for this claim comes from studies that ask participants to make moral judgments while experimentally manipulating Type 2 processing. This paper presents a meta-analysis of the published psychological literature on the effect of four standard cognitive-processing manipulations (cognitive load; ego depletion; induction; time restriction) on moral judgments about sacrificial moral dilemmas [n = 44; k = 68; total N = 14, 003; M(N) = 194.5]. The overall pooled effect was in the direction predicted by the mDPM, but did not reach statistical significance. Restricting the dataset to effect sizes from (high-conflict) personal sacrificial dilemmas (a type of sacrificial dilemma that is often argued to be best suited for tests of the mDPM) also did not yield a significant pooled effect. The same was true for a meta-analysis of the subset of studies that allowed for analysis using the process dissociation approach [n = 8; k = 12; total N = 2, 577; M(N) = 214.8]. I argue that these results undermine one important line of evidence for the mDPM and discuss a series of potential objections against this conclusion.